2011
DOI: 10.1039/c0nr00940g
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of transparent and conductive thin films of single-walled carbon nanotubes

Abstract: Single-walled carbon nanotubes (SWNTs), synthesized using the arc-discharge method and the direct-injection-pyrolytic synthesis (DIPS) method, were dispersed in a tetrahydrofuran solution containing propylamine and used to prepare transparent and conductive thin films on PET films using an airbrush technique. The SWNTs were analyzed using vis-near infrared absorption spectroscopy, Raman spectroscopy, scanning electron microscopy, and atomic force microscopy. The surface resistivity of the SWNT films on the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 35 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…Therefore, injection FCCVD has been proved to be an effective method for CNT synthesis. [32,[42][43][44][45] It is wellknown that the physical and chemical properties of SWCNTs are closely related to their diameters. Therefore, considerable effort has been devoted to controlling the size of catalyst particles and hence, the diameter of the grown SWCNTs.…”
Section: Catalyst Type and Feeding Methodsmentioning
confidence: 99%
“…Therefore, injection FCCVD has been proved to be an effective method for CNT synthesis. [32,[42][43][44][45] It is wellknown that the physical and chemical properties of SWCNTs are closely related to their diameters. Therefore, considerable effort has been devoted to controlling the size of catalyst particles and hence, the diameter of the grown SWCNTs.…”
Section: Catalyst Type and Feeding Methodsmentioning
confidence: 99%
“…The upward trend on the σ dc / σ oc value of SWNT TCFs with prolonged nitric acid treatment can be attributed to the increased functionalization of the SWNTs and the concomitant higher doping level. It is known from the literature that post‐treatment of SWNT films with HNO 3 improves the electrical conductivity through doping . Shin et al reported that TCFs fabricated from dispersion of SWNTs in N‐methylpyrrolidone solvent showed a significant decrease in R s from ca.…”
Section: Resultsmentioning
confidence: 99%
“…Since the preparation method for CNT‐based TCFs using filtration‐transfer and dip‐coating techniques was first reported by Wu et al and Saran et al, respectively, in 2004, several leading research groups and companies have put considerable effort into this area. Until now, many solution‐processing methods such as vacuum filtration followed by transfer printing, dip coating, spin coating, spray coating, electrophoretic deposition (EPD), printing (rod coating, inkjet printing, and slot coating) and, recently, brush painting have been developed to fabricate CNT‐based TCFs. Of course all of these methods have advantages and disadvantages.…”
Section: Transparent Conductive Electrodes (Tces)mentioning
confidence: 99%